Formulation of value added chicken nuggets using carrot and ginger as a source of dietary fiber and natural antioxidant: Value addition of chicken nuggets (SAARC Journal of Agriculture, 2022)
The study was aimed to evaluate the effect of different levels of carrot with ginger on the quality attributes of chicken nuggets. For this purpose, chicken meat samples were divided into four treatment groups viz. T0 (Control), T1 (1% ginger and 4% carrot), T2 (1% ginger and 8% carrot) and T3 (1% ginger and 12% carrot). Days of intervals were 0, 15, 30 and 45th days. Samples were preserved at -20º C for 45 days. An ANOVA of a 4×4 factorial experiment in completely randomized design having three replications per treatment was used for analyses of data. Sensory, proximate, physicochemical, biochemical and microbiological analyses were determined. Color, flavor, juiciness, tenderness and overall acceptability increased significantly (p